The consequences of environmental policy for economic growth: A numerical simulation of the transition path - Frank Hettich (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper analyses the consequences of tightening environmental policy for economic growth. To find out how the new balanced growth path is reached in the long run, we simulate numerically for the short and medium term the transition path of a change in environmental policy within an endogenous growth model. This enables us to analyse welfare effects also dynamically. Additionally, it is possible to compare accumulated levels of abatement, consumption, and output after the transition process with the business as usual scenario. Whereas long run growth rates are not affected by any environmental measure, there are non-monotonous adjustments during the transition. For environmental policy being suboptimal in the initial equilibrium, welfare in every period is higher compared to the business as usual scenario.
Keywords: 330; Umweltpolitik; Umweltökonomik; Neue Wachstumstheorie; Simulation; Wohlfahrtsanalyse; Theorie